Speech therapy approach to obstructive sleep apnea syndrome (OSAS) in children (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2021)
INTRODUCTION: Obstructive Sleep Apnea Syndrome (OSAS) is one of the most common respiratory complications in children. Its treatment involves an interdisciplinary team of healthcare professionals, including a speech therapist, who must develop strategies for detection, diagnosis, and intervention that, from their field, can improve the quality of life of children and their families. METHODS: A systematic literature review was carried out following the Prisma methodology. The questions were organized according to the PICO question framework, and the articles were selected using the PRISMA methodology. RESULTS: The articles were subjected to a selection, screening, and inclusion process following the PRISMA flowchart, resulting in 60 articles that answered the research question. ANALYSIS AND DISCUSSION: A large number of studies agree in stating that obstructive sleep apnea (OSAS) is one of the most common problems in children that had not been taken into account and that it is arousing increasing interest. Questionnaires and protocols have been validated nationally and internationally to help measure each of the factors involved in OSAS, enabling interventions to reduce symptoms. CONCLUSIONS: Speech therapy for OSAS requires a specific assessment framework that allows for timely diagnosis and lays the groundwork for effective intervention based on myofunctional therapy and sleep postural modifications, combining strategies aimed at achieving neuromuscular balance.
Keywords: Speech Therapy; Obstructive Sleep Apnea; Questionnaires